2020
DOI: 10.1103/physrevb.102.094105
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative understanding of negative thermal expansion in scandium trifluoride from neutron total scattering measurements

Abstract: Negative thermal expansion (NTE)-the phenomenon where some materials shrink rather than expand when heated-is both intriguing and useful but remains poorly understood. Current understanding hinges on the role of specific vibrational modes, but in fact thermal expansion is a weighted sum of contributions from every possible mode. Here we overcome this difficulty by deriving a real-space model of atomic motion in the prototypical NTE material scandium trifluoride, ScF 3 , from total neutron scattering data. We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 72 publications
2
36
0
Order By: Relevance
“…The difference in flexibility with respect to distortions of the O-Re-O (F-Sc-F) bond angle is smaller than that for distortions of the Re-O-Re (Sc-F-Sc) linkage. However, molecular dynamics simulations have shown that the sign of the coefficient of thermal expansion is more sensitive to changes in the force constant governing the former 24 . Another difference of note is that the trends in the X-M -X bond angle for ReO 3 and ScF 3 are opposed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference in flexibility with respect to distortions of the O-Re-O (F-Sc-F) bond angle is smaller than that for distortions of the Re-O-Re (Sc-F-Sc) linkage. However, molecular dynamics simulations have shown that the sign of the coefficient of thermal expansion is more sensitive to changes in the force constant governing the former 24 . Another difference of note is that the trends in the X-M -X bond angle for ReO 3 and ScF 3 are opposed.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to typical ABX 3 perovskites, which also exhibit rigid rotations of the octahedral units, ReO 3 and ScF 3 both have a vacant A-site, allowing larger tilt angles 19 . Recent analysis of the local structure of ScF 3 23,24 demonstrated that flexibility of the octahedra themselves, i.e., distortions of the intraoctrahedral F-Sc-F bond angles away from 90 • , is a key contributor to the NTE. In perovskites, pure RUMs are restricted to the line M-R in reciprocal space, which in principle gives their mode Grüneisen parameters a vanishingly small contribution towards the mean Grüneisen parameter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A low energy cost for scissoringtype deformations of the octahedra would increase the proportion of quasi-RUMs, modes of mixed RUM and octahedral deformation character, with negative Grü neisen parameters. Both of these possibilities are analysed further in our (Bird et al, 2020) and others' recent work (Dove, 2019;Dove et al, 2020).…”
Section: Scandium Trifluoridementioning
confidence: 86%